Anxiety Of Nick O'Bannon In David R Ellis' Rest In Pieces Final Destination 4 Movie (2009): A Psychoanalytic Approach - Anshori, Yusuf; , Drs. Abdillah Nugroho. M. Hum; , Drs. Sigit Haryanto, M. Hum (2013)
The problem of this study is anxiety of Nick O'Bannon reflected in Final Destination 4 movie directed by David R. Ellis. The objective of this study is to analyze the movie based on the structural elements and to analyze the movie based on the psychoanalytic approach. The type of this research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is final destination movie directed by David R. Ellis in 2009. While the secondary data sources are other materials taken from books, author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the writer portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, mise-en scene, casting cinematography, sound, and editing are supporting each other to produce a good quality movie. Second, based on the psychoanalytic analysis, the study shows that the problem faced by major character is his own psychological condition to decide the appropriate ways for his life. This movie also shows the process that involves supernatural power will produce the amazing result